The Influence of the Teams Games Tournament (TGT) Cooperative Learning Model on Grade X Students’ Learning Outcomes in Learning the Basic Laws of Chemistry at SMAN 1 Sungayang - Kurnia Hayati; Mimi Herman (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study was conducted to examine the effect of the Teams Games Tournament (TGT) cooperative learning model on the learning outcomes of tenth-grade students at SMA Negeri 1 Sungayang in the topic of the basic laws of chemistry. The novelty of this research is reflected in the integration of the TGT model with academic games and tournament-based activities designed to enhance students’ engagement and conceptual understanding in chemistry instruction. This study applied a quasi-experimental approach using a nonequivalent control group design. The population comprised all tenth-grade students, with two classes selected as samples through purposive sampling. The experimental group was taught using the TGT cooperative learning model, while the control group received conventional instruction. Data were collected using pretest and posttest instruments that had previously undergone validity and reliability testing. The data analysis included tests of normality and homogeneity, N-gain analysis, and an independent samples t-test. The findings revealed that the experimental class achieved an N-gain score of 0.303, which falls into the moderate category, whereas the control class obtained an N-gain score of 0.089, categorized as low. The hypothesis testing showed a significance value below 0.05 with a t-value of −7.154, indicating a statistically significant difference in learning outcomes between the two groups. These results demonstrate that the TGT cooperative learning model has a significant positive effect on students’ learning outcomes. Furthermore, its implementation promotes active student involvement, collaborative learning, increased motivation, and deeper conceptual understanding, which collectively contribute to improved academic achievement.